KARAKTERISTIK MORFOLOGI, BIOKIMIA, DAN MOLEKULER ISOLAT KHAMIR IK-2 HASIL ISOLASI DARI JUS BUAH SIRSAK (Annona muricata L.) - Vivi Suryaningsih; Rejeki Siti Ferniah; Endang Kusdiyantini (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2018)
Yeast was found in foods that contain lots of sugar as fruits. Yeast utilizes simple sugars in food to gain energy. Yeast has a role in the natural fermentation of the fruit that resulting of decay, discoloration, and cause the fruit not durable. The purpose of this research were to isolate the yeast from the soursop fruit and to identify the yeast in morphology, biochemistry, and molecular test based on Internal Transcribed Spacer (ITS). Isolation of yeast was performed by growing on medium PDA and chloramphenicol. Identification was done through biochemical test by looking at the capabilities in the fermentation of carbohydrate and the abilities to grow on a medium to high osmotic pressure. Molecular identification was done using Internal Transcribed Spacer (ITS) region. The result showed that isolate IK-2 yeast from the soursop fruit juice had a distinctive form round to oval, prominent elevation, the colour creamy white, form a buds, able to ferment glucose and sucrose, but not able to ferment lactose, as well as being able to grow on media with glucose level 50 %. Molecular analysis of the ITS region using ITS1 and ITS4 primers, and phylogenetic analysis using Neighbor Joining. The result of the Basic Local Alignment Tools (BLAST) showed that the isolate had 95% homology with Candida tropicalis. Key Words : Yeast, Soursop (Annona muricata L.), Internal Transcribed Spacer (ITS)